Irenaeus an introduction - Minns, Denis (London ; New York : T & T Clark, 2010)
Irenaeus of Lyons (c. 130-200) has been called 'the first great Catholic theologian'. As this book explains, the description is accurate, since the Christianity represented by Irenaeus is recognizably that of the Catholic Church, though unfamiliar in its primitiveness. The thought of Irenaeus represents an important stage in the development of Christian orthodoxy. This is a general introduction to the theology of Irenaeus. Readers will find it comprehensive, informative, lucid, and elegantly written. It is especially welcomed by those able to read only English, for it is the first general book
Introduction -- Heresies -- The one God -- Knowing the one God as Father, Son and Holy Spirit -- The divine plan of salvation -- From Adam to Christ -- From Christ to the kingdom -- Conclusion.
Previous ed.: 1994.
Includes bibliographical references (p. 159-167) and indexes.
Description based on print version record.
Keywords: Irenaeus, -- Saint, Bishop of Lyon; Theology, Doctrinal -- History -- Early church, ca. 30-600.; Religion; RELIGION -- Christianity -- General; RELIGION -- Christian Theology -- Systematic; Electronic books